STOPS approach to individualised physiotherapy versus usual physiotherapy care for chronic low back pain in India: A randomised controlled trial protocol - Andrew J. Hahne; Mohini Shah; Muhammed Rashid; Kavitha Raja; Musa Sani Danazumi; Jon Ford (PLoS ONE, 2025)
Background Low back pain (LBP) is the leading cause of disability worldwide, particularly in low- and middle-income countries such as India. Many treatment approaches fail to address the multidimensional nature of LBP, leading to suboptimal outcomes. The Specific Treatment of Problems of the Spine (STOPS) approach addresses biological, neurophysiological, and psychosocial factors to deliver individualised physiotherapy for LBP, yet its effectiveness in India has not been explored. Objective This study aims to evaluate the effectiveness of individualised physiotherapy using the STOPS approach compared to usual physiotherapy care in individuals with chronic low back pain (CLBP) in India. Methods This is a parallel-group superiority randomised controlled trial with blinding of participants, outcome assessors, and the data analyst. A total of 154 participants in India with CLBP will be recruited and randomised to receive 11 sessions of either individualised physiotherapy via the STOPS approach or usual physiotherapy care. The primary outcome is activity limitation measured using the Oswestry Disability Index at 26 weeks. Functional MRI and qualitative interviews will assess brain functional changes and participant experiences, respectively. Data will be analysed using intention-to-treat principles. Conclusion This study will provide insights into the effectiveness of the STOPS approach to delivering individualised physiotherapy for CLBP in India, in comparison to usual physiotherapy care. Trial registration This trial is prospectively registered with the Clinical Trials Registry of India: CTRI/2024/08/072259, https://ctri.nic.in/Clinicaltrials/pmaindet2.php?EncHid=MTAyNjY2&Enc=&userName=2024/08/072259